A Variable-Width Strip Dipole-Based Leaky-Wave Antenna Using Spoof Surface Plasmon Polaritons - Jatav R.; Mali R.; Meshram M.K. (My University, 2025)
A high-gain, low-profile, and compact-size single-port leaky-wave antenna powered by spoof surface plasmon polaritons (SSPPs) based line is proposed. The proposed leaky-wave antenna is implemented using a variable-width strip dipole on either side of the spoof surface plasmon polaritons line. The designed antenna consists of a coplanar waveguide (CPW), a transition section, and a strip dipole-loaded SSPPs line. To validate the simulation results, a prototype of the single-port leaky-wave antenna is fabricated and measured. The simulation and measured results are in unison. The designed antenna covers the frequency range of 6.18 - 11.40 GHz. The single-port antenna provides the beam-scanning span of 55∘(-32∘to+23∘) with a significant gain in the broadside direction. The average realized gain in the scanning range is 11.05 dBi, while the peak realized gain and radiation efficiency are 13.8 dBi and 95%, respectively. The designed antenna is intended to be used as a low-profile antenna for radar and wireless communications. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.